Hypnotherapy for irritable bowel syndrome: an audit of one thousand adult patients. Issue 9 (4th March 2015) - Miller, V.; Carruthers, H. R.; Morris, J.; Hasan, S. S.; Archbold, S.; Whorwell, P. J.
Summary Background Gut‐focused hypnotherapy improves the symptoms of irritable bowel syndrome (IBS) with benefits being sustained for many years. Despite this, the technique has not been widely adopted by healthcare systems, possibly due to relatively small numbers in published studies and uncertainty about how it should be provided. Aim To review the effect of hypnotherapy in a large cohort of refractory IBS patients. Methods One thousand IBS patients fulfilling Rome II criteria, mean age 51.6 years (range 17–91 years), 80% female, receiving 12 sessions of hypnotherapy over 3 months, were studied. The primary outcome was a 50 point reduction in the IBS Symptom Severity Score. The fall in scores for Noncolonic Symptoms, Quality of Life and Anxiety or Depression, were secondary outcomes. The Federal Drug Administration's recommended outcome of a 30% or more reduction in abdominal pain was also recorded. Results Overall, 76% met the primary outcome which was higher in females (females: 80%, males: 62%, P < 0.001) and those with anxiety (anxious: 79%, non‐anxious: 71%, P = 0.010). The mean reduction in other scores was: IBS Symptom Severity Score, 129 points (P < 0.001), Noncolonic Symptom Score, 65 (P < 0.001) and Quality of Life Score, 66 (P < 0.001). Sixty‐seven per cent reported a 30% or more reduction in abdominal pain scores. Pain days fell from 18 to 9 per month. Patients with anxiety and depression fell from 63% to 34% and 25% to 12% respectively (P < 0.001). Outcome was unaffected by bowel habit subtype. Conclusion These results provide further evidence that gut‐focused hypnotherapy is an effective intervention for refractory IBS.